Heterogeneity of human corneal endothelium implicates lncRNA NEAT1 in Fuchs endothelial corneal dystrophy - Qun Wang; Shengqian Dou; Bin Zhang; Hui Jiang; Xia Qi; Haoyun Duan; Xin Wang; Chunxiao Dong; Bi Ning Zhang; Lixin Xie; Yihai Cao; Qingjun Zhou; et al. (Elsevier, 2022)
The corneal endothelium is critical for maintaining corneal clarity by mediating hydration through barrier and pump functions. Progressive loss of corneal endothelial cells during aging has been associated with the development of Fuchs endothelial corneal dystrophy (FECD), one of the main causes of cornea-related vision loss. The mechanisms underlying FECD development remain elusive. Single-cell RNA sequencing of isolated healthy human corneas discovered 4 subpopulations of corneal endothelial cells with distinctive signatures. Unsupervised clustering analysis uncovered nuclear enriched abundant transcript 1 (NEAT1), a long non-coding RNA (lncRNA), as the top expressed gene in the C0-endothelial subpopulation, but markedly downregulated in FECD. Consistent with human corneas, a UVA-induced mouse FECD model validated the loss of NEAT1 expression. Loss of NEAT1 function by an in vivo genetic approach reproduced the exacerbated phenotype of FECD by ablating corneal endothelial cells. Conversely, gain of function by a CRISPR-activated adenoviral delivery system protected corneas from UVA-induced FECD. Our findings provide novel mechanistic insights into the development of FECD, and targeting NEAT1 offers an attractive approach for treating FECD.